The lowermost Tejo River terrace at Foz do Enxarrique, Portugal: a palaeoenvironmental archive from c. 60–35 ka and its implications for the Last Neanderthals in Westernmost Iberia - Cunha, Pedro (2019)
Reconstruction of Pleistocene environments and processes in the sensitive geographical location of westernmost Iberia, facing the North Atlantic Ocean, is crucial for understanding impacts on early human communities. We provide a characterization of the lowest terrace (T6) of the Lower Tejo River, at Vila Velha de Rodao (eastern central Portugal). This terrace comprises a lower gravel bed and an upper division consisting of fine to very fine sands and coarse silts. We have used a multidisciplinary approach, combining geomorphology, optically stimulated luminescence (OSL) dating, grain-size analysis and rock magnetism measurement, in order to provide new insights into the environmental changes coincident with the activity of the last Neanderthals in this region. In addition, we conducted palynological analysis, X-ray diffraction measurement and scanning electron microscopy coupled with energy dispersive spectra of the clay fraction and carbonate concretions. We discuss these new findings in the context of previously published palaeontological and archeological data. The widespread occurrence of carbonate concretions and rizoliths in the T6 profile is evidence for episodic pedogenic evaporation, in agreement with the rare occurrence and poor preservation of phytoliths. We provide updated OSL ages for the lower two Tejo terraces, obtained by post infra-red stimulated luminescence: (i) T5 is c. 140 to 70 ka; (ii) T6 is c. 60 to 35 ka. The single archaeological and fossiliferous level located at the base of the T6 upper division, recording the last regional occurrence of megafauna (elephant and rhinoceros) and Mousterian artefacts, is now dated at 44 +/- 3 ka. With reference to the arrival of Neanderthals in the region, probably by way of the Tejo valley (from central Iberia), new dating suggests a probable age of 200-170 ka for the earliest Mousterian industry located in the topmost deposits of T4.